Production Systems - Florida Greenhouse Vegetable Production Handbook, Vol 2: HS777/CV255, 11/2018 - Hochmuth, George (EDIS, 2018)
In any fertigation system, the basic components are: stock tanks for fertilizers, a water source, a method for mixing fertilizer and water in correct proportion, and a pump to move the water and fertilizer mix to the plants. The method in which these components are arranged and used differs depending on the specific cultural system used. This document is about those components of fertigation, the process of apply fertilizers with the irrigation water. First published in 1990.